Effect of irinotecan on HMGB1, MMP9 expression, cell cycle, and cell growth in breast cancer (MCF-7) cells - Saeedeh Keyvani-Ghamsari; Azra Rabbani-Chadegani; Javad Sargolzaei; Maryam Shahhoseini (Tumor Biology)
Irinotecan is a natural alkaloid agent widely used in cancer therapy. High-mobility group protein B1 as a non-histone chromosomal protein plays a fundamental role in gene expression and inflammation. In this study, the effect of irinotecan on high-mobility group protein B1 and MMP9 content, gene expression, cell cycle, and cell growth in human breast cancer cells (MCF-7) was investigated. The cells were exposed to various concentrations of irinotecan and the viability determined by trypan blue exclusion and 3-(4,5-dimethylthiazal-2-yl)-2,5-diphenyltetrazolium bromide assays. High-mobility group B proteins were extracted from the control and drug-treated cells and analyzed by immunoblot. High-mobility group protein B1 and MMP9 messenger RNA expression was studied by reverse transcription polymerase chain reaction. The results demonstrated reduction of cell viability upon increasing irinotecan concentration, up-regulated high-mobility group protein B1 gene expression, and down-regulated MMP9 mRNA. Although the content of high-mobility group protein B1 was decreased in chromatin extract upon drug action, no high-mobility group protein B1 release to extracellular space was detected by immunoblot analysis. Irinotecan decreased H3K9 acetylation and increased poly ADP-ribose polymerase fragmentation to 89 kDa and anion superoxide production suggesting induction of apoptosis in these cells. Propidium iodide staining of the cells 24 h after the drug treatment revealed arrest of the cells in S-phase. From the results, it is concluded that overexpression of high-mobility group protein B1 in the presence of irinotecan precedes breast cancer cells into apoptosis and in this response the binding of irinotecan to chromatin or high-mobility group protein B1 may condense/aggregate chromatin, preventing high-mobility group protein B1 release from chromatin.